Ø§Ù„Ù…Ø°Ù‡Ø¨ Ø§Ù„Ø´Ø§ÙØ¹ÙŠ ÙÙŠ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§Ø› ØªØ£Ø±ÙŠØ®Ù‡ Ùˆ Ø¢Ø«Ø§Ø±Ù‡ - Muhammad Ikhsan (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2020)
This study aims to identify the extent to which the historical roots of the Shafi'i school in Indonesia in terms of its arrival and spreading and to determine the extent of the influence of the Shafi'i school in the lives of Muslims in Indonesia and whether it plays a role in the codification of laws in Indonesia? The researcher employed the historical inductive approach and the descriptive-analytical approach. Among the results of the research are that the entry of the Shafi'i school in Indonesia was accompanied by the entry of Islam in it by Arab traders from the Arabian Peninsula - or the Indies (Malibar and Gujarat). Based on reliable documents, I can confirm that Islam entered Indonesia in the seventh century AD (first century in Hijriyah), yet began to spread strongly in the tenth century AD through the emergence of Islamic kingdoms in the archipelago which adopted the Shafi'i school as the official school of the state. The influence of the Shafi'i school is evident in Indonesia on the educational curriculum taught in the era of the Islamic kingdoms and the era of independence in several institutions and Islamic boarding schools. The Shafi'i school also shows its influence in the law of Islamic governance in Indonesia, although it is limited to matters of marriage, inheritance, and waqf.